2018
DOI: 10.1186/s12909-018-1414-9
|View full text |Cite
|
Sign up to set email alerts
|

Geographical mobility of UK trainee doctors, from family home to first job: a national cohort study

Abstract: BackgroundThe UK faces geographical variation in the recruitment of doctors. Understanding where medical graduates choose to go for training is important because doctors are more likely to consider practicing in areas where they completed postgraduate training. The wider literature also suggests that there is a relationship between origin and background, and where doctors wish to train/work. Thus, the purpose of this paper is to investigate the geographical mobility of UK medical graduates from different socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The importance of locality in terms of training near friends and family is of interest. Many studies have shown that medical graduates typical migrate back home at some point in their careers 64‐66 . Our definition of location, developed via qualitative work, 7 specifically included reference to being near family and friends who are important in terms of social support.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of locality in terms of training near friends and family is of interest. Many studies have shown that medical graduates typical migrate back home at some point in their careers 64‐66 . Our definition of location, developed via qualitative work, 7 specifically included reference to being near family and friends who are important in terms of social support.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows, for example, strong connections between admission decisions by medical schools and the choices made by FY2 doctors about both specialty and place of work 78…”
mentioning
confidence: 99%
“…These data have been used to study outcomes and progression in medical specialties and foundation programme extensively and have been shown to be reliable. [13][14][15] Patient and public involvement Patient and public involvement was not sought given the educational nature of the study and the fact no patients were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…These data can be modelled to assess the differences in ARCP outcomes between surgical specialties. These data have been used to study outcomes and progression in medical specialties and foundation programme extensively and have been shown to be reliable 13–15…”
Section: Methodsmentioning
confidence: 99%